Eficiência do silicato de potássio no controle do oídio e no desenvolvimento de abobrinha de moita - Ramos, Anamaria Rp [UNESP]; Santos, Ricardo L Dos [UNESP]; Amaro, Amanda Cristina E [UNESP]; Fumes, Leandro Augusto A [UNESP]; Boaro, Carmen Silvia F [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (Associação Brasileira de Horticultura, 2013)
The most widely standard used for powdery mildew control on cucurbitaceas is the use of resistant cultivars and systemic fungicides, even though nutrition has been an option. The supply of silicon is benefic to many vegetable species, stimulating growth, yield, photosynthesis and regulation of transpiration; besides, its deposition in the epidermis avoids the invasion of fungus, bacteria and sucking insects. The aim of this experiment was to evaluate the influence of potassium silicate on powdery mildew control, development and yield of zucchini squash, cultivar Caserta. The experiment was conducted at Universidade Estadual Paulista, in greenhouse conditions and with a randomized design, divided in four replications, 11 plants per plot and five treatments: control (water), chemical treatment with fenarimol (2.4 g a.i. 100 L-1) and potassium silicate, in doses 1.5 L ha-1; 2.0 L ha-1 and 2.5 L ha-1. We evaluated the disease severity; gas exchange (net CO2 assimilation rates, transpiration, stomatal conductance and water use efficiency); growth (leaf area ratio, relative growth rate, absolute growth rate, net assimilation rate and specific leaf mass) and yield. The results showed that the foliar application of potassium silicate and fenarimol controlled powdery mildew and had no influence on plant growth. Therefore, the potassium silicate may be used as alternative for control of fungal pathogens and reduced application of chemical products, which provides a greater environmental sustainability. However, it is necessary to be careful with high doses because it was observed that 2.5 L h-1 was harmful to fruit production and gas exchange, despite being effective in controlling powdery mildew. According to this study it is recommended using 2.0 L ha-1 for control of powdery mildew to zucchini squash, and can replace the use of fenarimol, without affecting productivity and development of plants.

A medida mais utilizada para o controle de oídio em cucurbitáceas é o uso de variedades resistentes e fungicidas sistêmicos, entretanto, a nutrição silicatada tem se mostrado uma opção. O fornecimento do silício é benéfico para muitas espécies vegetais, estimulando o crescimento, a produção, a fotossíntese e a regulação da transpiração; além disso, sua deposição na epiderme evita a invasão de fungos, bactérias e insetos sugadores. O objetivo deste trabalho foi verificar a influência do silicato de potássio no controle do oídio, e no desenvolvimento e na produção de abobrinha de moita, cultivar Caserta. O experimento foi conduzido em cultivo protegido, com delineamento inteiramente casualizado, quatro repetições e cinco tratamentos: testemunha (água); tratamento químico com fenarimol (2,4 g i.a 100 L-1) e silicato de potássio, nas doses de 1,5 L ha-1; 2,0 L ha-1 e 2,5 L ha-1. Foram avaliados a severidade da doença; trocas gasosas; crescimento e produção de frutos. Os resultados mostraram que a aplicação foliar de silicato de potássio com fenarimol controlou o oídio e não teve influência no crescimento da planta. Portanto, o silicato de potássio pode ser utilizado como alternativa para o controle desse fungo e diminuição da aplicação de produtos químicos, o que proporciona uma maior sustentabilidade ambiental. No entanto, deve-se tomar cuidado com dosagens altas, pois observou-se que a dosagem de 2,5 L ha-1 foi prejudicial à produção de frutos e às trocas gasosas, apesar de ter sido eficiente no controle do oídio. Recomenda-se o uso de 2,0 L ha-1 de silicato de potássio para o controle de oídio para abobrinha de moita, podendo substituir o uso de fenarimol, sem afetar a produção e desenvolvimento das plantas.
Efficiency of potassium silicate in powdery mildew control and development of summer squash
Keywords: Cucurbita pepo; Podosphaera xanthii; silício; trocas gasosas; Cucurbita pepo; Podosphaera xanthii; silicon; gas exchanges